The effect of information seeking behavior on online database usage among the undergraduate students - Zulkifli, Zahidah; Mat Surin, Ely Salwana; Salahuddin, Ashraf Ali; M. Daud, Norhidayah (Akademiai Kiado Rt., 2019)
Every year the library of IIUM subscribes a quite number of online databases with huge expenses but the utilization of these databases is countable. 10 out of 53 subscriptions have been terminated by 2015 to save the cost go in vain. The purpose of this paper is to develop a model based on the ISB elements to identify the reason behind this less usage and to increase the usage of online databases in future. It has undertaken a quantitative approach to identify the elements of ISB among undergraduate (UG) students. The primary data has been collected through questionnaires based on the variables identified in the objective. There are 118 samples participated in this research and the proposed model has been adapted from Savolainen and Thomas D. Wilson. Psychological perception, searching strategies and the information resources have been considered as the independent variable and measured the usage of the online database among UG students as the dependent variable. The results have shown that there are seven elements which have an influence on the usage of the online database among IIUM UG students. Despite the limited number of samples and a specific group of students, the proposed model can enhance the usage of online database system subscribed by IIUM library as well a search engine can be developed to get the usage increased. In that sense, it is recommended to involve more participants from the different level of students and users to get diverse elements of ISB. However, the paper contributes to bridge the gap between the online database usage and the users which is to believe an effective outcome for online database subscription. It is hoped that the proposed model would significantly fill this gap and help the library to increase more users for their expensive databases.